The Preoccupation of the United Nations with Israel: Evidence and Theory - Raphael N. Becker; Arye L. Hillman; Niklas Potrafke; Alexander H. Schwemmer (Center for Economic Studies and ifo Institute (CESifo), 2014)
We compiled data on all United Nations General Assembly resolutions on which voting took place between January 1990 and June 2013 and find a preoccupation with one country: in 65 percent of instances in which a country is criticized in a resolution, the country is Israel, with no other country criticized in more than 10 percent of resolutions. We use comparative quantitative criteria to confirm that Israel is subject to discrimination. To explain the motives for discrimination, we present a model of behavioral political economy that includes decoy voting, vanity of autocrats, and a Schelling focal point for deflection of criticism. The model includes a role for traditional prejudice. Our conclusions more generally concern political culture in the United Nations.
Keywords: Z12; 330; United Nations General Assembly voting; expressive voting; decoy voting; focal point; logrolling; discrimination; prejudice; political culture